POTENSI PEWARNA ALAMI TEKSTIL DI KEBUN RAYA SRIWIJAYA (STUDI PENGARUH AIR GAMBUT TERHADAP KECERAHAN WARNA DARI TUMBUHAN BEGONIA (BEGONIA SP.) DAN SEDUDUK (MELASTOMA MALABATHRICUM L.)) - Sri Maryani; Oom Komalasari; Niken Probowati Nur Rahayu; Tri Novayanti Suswara (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Sources of natural dyes that are currently becoming an attractive choice in textiles encourage various parties to search for and develop it. A variety of plants that have the potential as sources of natural dyes in various regions, including South Sumatera Province, is rich in various plants, both dry and wetlands. Sriwijaya Botanical Garden as one of the regions in South Sumatra Province, which stores various plant species, also has a potential source of natural dyes, namely Begonia (Begonia Sp) and seduduk (Melastoma malabathricum L.). This research is experimental research conducted in January-May 2020. Based on observation, it can be concluded that the brightness of the colors produced on the fabric can be obtained by using mineral water, while to produce a darker color can be used peat water. The type of binding agent used can also affect the resulting color's appearance to increase the diversity of colors made from natural ingredients. In the future, the resulting color's chemical content test is essential so that it can be developed as a natural dye in the textile industry.